Phase structure and electrochemical performance of layered-spinel integrated LiNi0.5Mn0.5O2-LiMn1.9Al0.1O4 composite cathodes for lithium ion batteries. Issue 15 (15th November 2016) - Tian, Mijie; Zhou, Lin; Wu, Huali; Jiang, Na; Zheng, Qiaoji; Xu, Chenggang; Lam, Kwok Ho; Lin, Dunmin
Abstract: In recent years, multi-component integrated composite cathodes for lithium ion batteries have attracted considerable attention. In this work, novel layered-spinel integrated cathode materials of (1− x )LiNi0.5 Mn0.5 O2 - x LiMn1.9 Al0.1 O4 were synthesized by a sol-gel method, and their phase structures, morphologies and electrochemical performance were investigated. The crystal structure of the (1− x )LiNi0.5 Mn0.5 O2 - x LiMn1.9 Al0.1 O4 is changed from layered to spinel structure with increasing x . All the samples exhibit nanoscale grains with the minimum grain size of 130 nm when x = 0.5. The composite electrode with x = 0.5 exhibits the optimal discharge capacity, presenting a large initial discharge capacity of 236 mAh g −1 at the current density of 20 mA g −1 . Good rate capability is also obtained at the composite electrode with x = 0.5 where the electrode displays the relatively high discharge capacity of 64.9 mAh g −1 at the high rate of 5 C. The improved electrochemical performance is related to the introduction of spinel structure into layered structure and small grain size. The spinel structure can stabilize the layered structure, which leads to the improvement in the electrochemical performance of the composites; and the small grain size in the sample with x = 0.5 provides short lithium ion diffusion way and thus enhances the electrochemical performance.